Innovative polyelectrolytes/poly(ionic liquid)s for energy and the environment. Issue 8 (7th March 2017) - Ajjan, Fátima N; Ambrogi, Martina; Tiruye, Girum Ayalneh; Cordella, Daniela; Fernandes, Ana M; Grygiel, Konrad; Isik, Mehmet; Patil, Nagaraj; Porcarelli, Luca; Rocasalbas, Gillem; Vendramientto, Giordano; Zeglio, Erica; et al.
Abstract: This paper presents the work carried out within the European project RENAISSANCE‐ITN, which was dedicated to the development of innovative polyelectrolytes for energy and environmental applications. Within the project different types of innovative polyelectrolytes were synthesized such as poly(ionic liquid)s coming from renewable or natural ions, thiazolium cations, catechol functionalities or from a new generation of cheap deep eutectic monomers. Further, macromolecular architectures such as new poly(ionic liquid) block copolymers and new (semi)conducting polymer/polyelectrolyte complexes were also developed. As the final goal, the application of these innovative polymers in energy and the environment was investigated. Important advances in energy storage technologies included the development of new carbonaceous materials, new lignin/conducting polymer biopolymer electrodes, new iongels and single‐ion conducting polymer electrolytes for supercapacitors and batteries and new poly(ionic liquid) binders for batteries. On the other hand, the use of innovative polyelectrolytes in sustainable environmental technologies led to the development of new liquid and dry water, new materials for water cleaning technologies such as flocculants, oil absorbers, new recyclable organocatalyst platforms and new multifunctional polymer coatings with antifouling and antimicrobial properties. All in all this paper demonstrates the potential of poly(ionic liquid)s for high‐value applications in energy and enviromental areas. © 2017 Society of Chemical Industry Abstract : This review presents the work carried out within the European project RENAISSANCE‐ITN which was dedicated to the development of innovative polyelectrolytes for energy and environmental applications.